2017
DOI: 10.5194/acp-17-10435-2017
|View full text |Cite
|
Sign up to set email alerts
|

Advanced error diagnostics of the CMAQ and Chimere modelling systems within the AQMEII3 model evaluation framework

Abstract: Abstract. The work here complements the overview analysis of the modelling systems participating in the third phase of the Air Quality Model Evaluation International Initiative (AQMEII3) by focusing on the performance for hourly surface ozone by two modelling systems, Chimere for Europe and CMAQ for North America.The evaluation strategy outlined in the course of the three phases of the AQMEII activity, aimed to build up a diagnostic methodology for model evaluation, is pursued here and novel diagnostic methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 54 publications
(71 reference statements)
2
15
0
Order By: Relevance
“…Furthermore, Mészáros et al (2009) pointed out that variation in surface resistance can involve differences in variability in total deposition velocity of up to 2 or 3 times, also indicating soil moisture as a key variable controlling the O 3 dry deposition. Moreover, our results are in agreement with Solazzo et al (2017), which created a diagnostic methodology for model evaluation; using CHIMERE, they showed that setting the ozone dry deposition velocity to zero causes a profound change of the error structure of O 3 concentration with significant impacts on not only the bias but also the variance and covariance terms (Solazzo et al, 2017). All these studies highlight that more sophisticated parameterizations of stomatal conductance are required in deposition models to reduce their uncertainty.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, Mészáros et al (2009) pointed out that variation in surface resistance can involve differences in variability in total deposition velocity of up to 2 or 3 times, also indicating soil moisture as a key variable controlling the O 3 dry deposition. Moreover, our results are in agreement with Solazzo et al (2017), which created a diagnostic methodology for model evaluation; using CHIMERE, they showed that setting the ozone dry deposition velocity to zero causes a profound change of the error structure of O 3 concentration with significant impacts on not only the bias but also the variance and covariance terms (Solazzo et al, 2017). All these studies highlight that more sophisticated parameterizations of stomatal conductance are required in deposition models to reduce their uncertainty.…”
Section: Discussionsupporting
confidence: 86%
“…This result is in agreement with a previous study which showed how, within CHIMERE, the deposition not only acts as a shifting term on the modelled concentration but also influences the variability and timing of ozone (Solazzo et al, 2017).…”
Section: Changes In the Model Performancessupporting
confidence: 93%
“…As we discussed in relation to the common model underestimation at Nagoya (Figure 4), further studies of the effects of meteorological parameters are needed, and this direction was also suggested by another model intercomparison study in Europe [31]. Another important factor is the vertical distribution of air pollutants simulated by the models.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 70%
“…In AQMEII, all participating groups were required to upload modeled hourly surface concentrations to the ENSEMBLE system at EC-JRC, at specified monitoring stations in EU and NA, as well as surface gridded data Im et al, 2015a, b;Solazzo et al, 2017b). This study investigates the impacts of emission perturbations and boundary conditions on O 3 , NO 2 , CO, SO 2 , PM 10 and PM 2.5 levels over Europe and North America.…”
Section: Emission Perturbationsmentioning
confidence: 99%
“…The model biases can be attributed to meteorology, in particular wind speed and planetary boundary layer (PBL) height, as well as the aerosol mechanisms used in different models that can underestimate either the inorganic aerosols (e.g., IT2) or the secondary organic aerosols (e.g., DK1), leading to underestimations in simulated PM mass. As discussed in Solazzo et al (2017b), the EU3 region that covers the central Europe including the Alps has the largest errors in terms of wind speed, mainly attributed to the diurnal component of the error, with some models having also large errors in the synoptic component. This region also represents the lowest correlation coefficients for all models.…”
Section: Model Evaluationmentioning
confidence: 99%